2020
DOI: 10.1093/rheumatology/keaa622
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship of serum nutritional factors with osteoarthritis: a Mendelian randomization study

Abstract: Objectives OA is the most common form of arthritis worldwide and has a major impact on the quality of life among the older population. This study aimed at determining the potential causal effects of several serum nutritional factors on OA. Methods A total of seven serum nutritional factors were identified from genome-wide association studies. Summary statistics for OA were obtained from UK Biobank (194 153 for women and 166 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 46 publications
8
33
0
Order By: Relevance
“…The 14 serum calcium SNPs were identified by a GWAS using 61,079 individuals of European descent ( O’seaghdha et al, 2013 ). These 14 serum calcium SNPs, especially the 8 SNPs at the genome-wide significance threshold, have been widely used as the potential instrumental variables to evaluate the association of serum calcium with other human complex diseases or phenotypes ( Larsson et al, 2017 , 2019 ; Xu et al, 2017 ; Meng et al, 2020 ; Wang Y. et al, 2020 ; Qu et al, 2021 ; Sun et al, 2021 ; Young et al, 2021 ; Yuan et al, 2021 ). Detailed information about these 14 SNPs is presented in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The 14 serum calcium SNPs were identified by a GWAS using 61,079 individuals of European descent ( O’seaghdha et al, 2013 ). These 14 serum calcium SNPs, especially the 8 SNPs at the genome-wide significance threshold, have been widely used as the potential instrumental variables to evaluate the association of serum calcium with other human complex diseases or phenotypes ( Larsson et al, 2017 , 2019 ; Xu et al, 2017 ; Meng et al, 2020 ; Wang Y. et al, 2020 ; Qu et al, 2021 ; Sun et al, 2021 ; Young et al, 2021 ; Yuan et al, 2021 ). Detailed information about these 14 SNPs is presented in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…As for other musculoskeletal diseases, a causal association between higher genetically predicted serum calcium levels and lower risk of osteoarthrosis (Odds ratio (OR): 0.67; P = 0.0044) was reported in a phenome-wide MR analysis 34 . A two-sample MR study found that serum calcium levels were also inversely associated with the risk of overall osteoarthritis (OR: 0.712; P = 1.84 × 10 −4 ), although this significant association was only detected in women (OR: 0.967; P = 0.038) 35 . Similar findings were found in a recent MR where a negative causal effect of higher serum calcium on localized osteoarthritis was reported (OR: 0.87, P = 0.021) 36 .…”
Section: Musculoskeletal Diseasesmentioning
confidence: 99%
“…Interestingly, this association was not supported by a meta-analysis published in 2015 where the authors used data from 7 RCTs (n= 51,111) and found no increased risk in calcium-treated patients for myocardial infarction in elderly women 44 . A large RCT involving women aged 50-79 years (n= 35,983) found no association between calcium plus vitamin D supplements and risk of heart failure 45 .…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Another MR analyses conducted by Qu et al (2020) showed that serum calcium levels were inversely associated with overall OA [OR 0.712, 95% CI (0.595, 0.850)]. According to a 48-month follow-up study, frequent milk consumption may be associated with reduced OA progression in women partially through elevated dietary calcium intake ( Lu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%